Lies my yaya should have told me RJ Ledesma's imaginary guide to whine and women. - Ledesma, R. J. (Rene J.) (Pasig City Anvil, 2008)
"With only words to use in his comedy, RJ approaches the challenge of lampooning love and its many forms in the same way that a true and serious writer would: with solid research related to the present context."--Publisher's description.
Love is a four-letter word -- The thin line between love and insanity -- Mating games -- The parent trap.
Keywords: Man-woman relationships -- Humor; Dating -- Philippines -- Humor; Courtship -- Philippines -- Humor; Philippine wit and humor